Using the Internet as a source of information during pregnancy — A descriptive cross-sectional study in Sweden. (September 2016) - Bjelke, Maria; Martinsson, Anna-Karin; Lendahls, Lena; Oscarsson, Marie
Abstract: Objective: The Internet plays a major role for pregnant women in seeking knowledge and for getting in touch with like-minded women. The information is available at all hours and can be accessed anywhere. The information provides the women with a sense of control and confidence but the large amount of information available can also be overwhelming. The aim of this study was to identify how women use the Internet as a source of information during their pregnancy and how it affects them. Design and setting: A descriptive cross-sectional study was conducted.Data were collected through a questionnaire at antenatal clinics in the southern Sweden. The data were analyzed descriptively Participants: A total of 193 Swedish women, pregnant at least 34 weeks, participated in the study. The response rate was 94%. Findings: Almost all (95%) of the women in the study used the Internet as a source of information. The main reason was to find information and read about people in the same situation. Reading pregnancy-related information on the Internet was seen as positive. However, a majority of the woman experienced feelings of worry due to something they read online. These feelings were most commonly coped with by talking to a partner, relatives, and friends or by asking the midwife at their next appointment. Eleven per cent of the women contacted the general healthcare services because of their feelings of worry. Conclusion: Almost all women in this study searched the Internet to find pregnancy-related information, despite being satisfied with the information they received from the ANC. Using the Internet was seen as complementary to the information from professionals. It also caused feelings of worry, which could lead to the woman contacting healthcare services for support. ANC could help to reduce these feelings for some women by informing about the advantages and disadvantages with online information and recommending suitable web pages.